2018
DOI: 10.1097/gox.0000000000001856
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Distraction Forces in the Mandible: Newton’s Third Law of Distraction

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…These data implied that the affected condyles rotated slightly post-MDO. When distracting the shortened ramus of the mandible in HFM, Shakir et al3 found that the proximal segment distracting force promoted counterclockwise rotation about the condyle and impacted on the TMJ. In another study, Master et al8 found that during the distraction period, a patient could posture the jaw forwards; this could be the result of pain or swelling in the joints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data implied that the affected condyles rotated slightly post-MDO. When distracting the shortened ramus of the mandible in HFM, Shakir et al3 found that the proximal segment distracting force promoted counterclockwise rotation about the condyle and impacted on the TMJ. In another study, Master et al8 found that during the distraction period, a patient could posture the jaw forwards; this could be the result of pain or swelling in the joints.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, mandibular distraction osteogenesis (MDO) had proven to be a powerful tool for the correction of HFM. 3 Mandibular distraction osteogenesis is associated with several irreplaceable advantages over traditional osteotomies and bone grafting for skeletal expansion. For example, the mandible can be lengthened at a young age and the soft tissues can adapt gradually due to the slow lengthening procedure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a concept, rebound therapy is based on the physical principles of bouncing such as kinetic energy, Hooke's law, Newton's third law and potential energy [7,8,9,10,11]. These properties lead to several biomechanical, physiological and therapeutic effects [11].…”
Section: Introductionmentioning
confidence: 99%